MODEL MANAJEMEN KURIKULUM BERBASIS KARAKTER DI PESANTREN : IMPLIKASINYA TERHADAP PEMBENTUKAN KEPRIBADIAN : Model Manajemen Kurikulum Berbasis Karakter di Pesantren, Implikasi terhadap Pembentukan Kepribadian Mahasiswa - Abdul Hamid (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
This study explores the character-based curriculum management model in the Nurul Jadid Islamic Boarding School, especially in the POMAS (Student Boarding School) Area. Using a qualitative approach, this study aims to understand how the implementation of a curriculum that emphasizes character formation affects the formation of students' personalities. Data is collected through observation, in-depth interviews, and document analysis, which are then analyzed to identify key patterns and themes. The results of the study show that the character-based curriculum at Nurul Jadid Islamic Boarding School includes Islamic values, discipline, and social responsibility, which significantly contribute to the personal development of students. The implementation of this curriculum has succeeded in creating a learning environment that supports the formation of strong characters and intact personalities, preparing students to become individuals with integrity and contribute positively to society.